Zinc Plasma Levels in Recurrent Vulvovaginal Candidiasis Patients - Deryne Anggia Paramita; Kristina Nadeak; Richard Hutapea (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Recurrent vulvovaginal candidiasis (RVVC) is episodes of thrush vulvovaginalis 4 times or more within 12 months.  Some exogenous pathogenic factors and host are known to be associated with RVVC including sex hormones, contraceptives, obesity, cellular immune responsses which could influenced by zinc. Purpose: To compare differences between plasma zinc levels of RVVC patients with controls. Methods: The study was cross involving 30 people with RVVC and 30 controls. Each study subjects vaginal smear examination and blood examination to measure the levels of zinc. Results: Mean value of plasma zinc levels in the case group (22.85 цg/dL) was lower than the control group (22.96 цg/dL). However, this difference was not statistically significant (p = 0.270). Conclusion: There is no difference between the plasma zinc level of vulvovaginalis recurrent candidiasis patients with controls.